A new genus and one new species of the family Uristidae Hurley, 1963 (Amphipoda, Lysianassoidea) described from hydrothermal vent of the Okinawa Trough, NW pacific - Wang, Yan-Rong; Sha, Zhong-Li (Zootaxa, 2024)
A new genus of the family Uristidae Hurley, 1963 is proposed, Liuiuristis gen. nov., with new species L. thermalis sp. nov. as the type species based on specimens collected by the expedition to hydrothermal vents on the Okinawa Trough. The new genus is characterized by the shape of accessory flagellum liking cap, the outer plate of the maxilla 1 having 11 setal-teeth, the gnathopod 1 parachelate in female and subchelate in male, the rami of the uropod 3 without plumose setae and the telson not cleft. K2P divergences of the mitochondrial COI gene in taxa attributed to Liuiuristis gen. nov. is presented.